2002
DOI: 10.1080/01443610120113382
|View full text |Cite
|
Sign up to set email alerts
|

Medical termination of missed abortion

Abstract: Missed abortions are a common occurrence and represent a heavy gynaecological emergency workload to both medical and nursing staff. The conventional method using vacuum aspiration of uterus is associated with morbidity and mortality. Medical termination of pregnancy is accepted as a safe and effective alternative method. However, medical evacuation of uterus in missed abortions had not been fully investigated. In this study we hope to examine the efficacy of medical methods for terminating missed abortions. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 10 publications
1
18
0
1
Order By: Relevance
“…This was not statistically significant. While other studies have confirmed procedure success using a follow-up ultrasound to rule out the presence of RPOC or to confirm endometrium thickness ˂ 15 mm [2,4,7], this was to our knowledge new information and is quite helpful in the counseling of our patients.…”
Section: Open Accessmentioning
confidence: 97%
See 2 more Smart Citations
“…This was not statistically significant. While other studies have confirmed procedure success using a follow-up ultrasound to rule out the presence of RPOC or to confirm endometrium thickness ˂ 15 mm [2,4,7], this was to our knowledge new information and is quite helpful in the counseling of our patients.…”
Section: Open Accessmentioning
confidence: 97%
“…Patient satisfaction is higher in patients treated with misoprostol compared to D & C [3,12]. Medically treated women experience a few more days of bleeding [7] and pain [2] controlled by either oral or intramuscular analgesia. Although there are clear differences in these managements, neither of the treatment options has been reported to affect future fertility [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Most of the reports shown misoprostol to be relatively safe for use in women with 1 st and 2 nd trimester and even in women with prior caesarean section . 42 Misoprostol is widely available. It is of low cost and stable at room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Transvaginal ultrasound was repeated after 24 h after the last dose and after expulsion of parts of conception to assure complete evacuation of the uterine cavity. The absence of remnant of conception or endometrial interface thickness less than 15 mm is mandatory to diagnose complete abortion [14].…”
Section: Methodsmentioning
confidence: 99%